Does Gender Make a Difference in Deception? The Effect of Transcranial Direct Current Stimulation Over Dorsolateral Prefrontal Cortex - Gao, Mei; Yang, Xiaolan; Shi, Jinchuan; Lin, Yiyang; Chen, Shu (Frontiers in Psychology, 2018)
Neuroimaging studies have indicated a correlation between dorsolateral prefrontal cortex (DLPFC) activity and deceptive behavior. We applied a transcranial direct current stimulation (tDCS) device to modulate the activity of subjects’ DLPFCs. Causal evidence of the neural mechanism of deception was obtained. We used a between-subject design in a signaling framework of deception, in which only the sender knew the associated payoffs of two options. The sender could freely choose to convey the truth or not, knowing that the receiver would never know the actual payment information. We found that males were more honest than females in the sham stimulation treatment, while such gender difference disappeared in the right anodal/left cathodal stimulation treatment, because modulating the activity of the DLPFC using right anodal/left cathodal tDCS only significantly decreased female subjects’ deception. In case that some senders may choose to tell the truth because they expect the receiver not to follow the message, an additional experiment and a post-experiment questionnaire were conducted. The results implied that most senders did not have such strategic consideration.